2017
DOI: 10.1073/pnas.1714579115
|View full text |Cite
|
Sign up to set email alerts
|

Ser7 of RNAPII-CTD facilitates heterochromatin formation by linking ncRNA to RNAi

Abstract: Some long noncoding RNAs (ncRNAs) transcribed by RNA polymerase II (RNAPII) are retained on chromatin, where they regulate RNAi and chromatin structure. The molecular basis of this retention remains unknown. We show that in fission yeast serine 7 (Ser7) of the C-terminal domain (CTD) of RNAPII is required for efficient siRNA generation for RNAi-dependent heterochromatin formation. Surprisingly, Ser7 facilitates chromatin retention of nascent heterochromatic RNAs (hRNAs). Chromatin retention of hRNAs and siRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…9a). rpb1-S7A slightly increased dg and dh RNAs in otherwise wild-type background, as expected 72 . However, in clr4∆ cells, rpb1-S7A reduced the levels of centromeric noncoding RNAs most prominently at imr3 where transcription levels are low.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…9a). rpb1-S7A slightly increased dg and dh RNAs in otherwise wild-type background, as expected 72 . However, in clr4∆ cells, rpb1-S7A reduced the levels of centromeric noncoding RNAs most prominently at imr3 where transcription levels are low.…”
Section: Resultssupporting
confidence: 83%
“…To obtain the direct evidence that RNAPII is involved in centromeric GCRs, we created the rpb1-S7A strain that harbored ChL. Consistent with low levels of H3K9me2 72 (Supplementary Fig. 8a), rpb1-S7A slightly increased GCR rate in otherwise wild-type background (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Transcripts from cnt::ura4 showed threefold reduction, while that of imr::ura4 showed about 1.4‐fold increase. As the levels of transcription at centromere region in wild‐type cell are quite low (about 1/1,000 of act1 gene, Figure d) and loss of heterochromatin caused 50‐ to 100‐fold increase in transcripts of marker genes inserted in centromeric heterochromatin (Kajitani et al., ), the observed changes of the amount of transcripts appear to be marginal. We also analyzed the localization of Cnp1 and H3K9me2 by ChIP assay to assess the effects of Sfh1 on centromeric chromatin structures (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…Because precipitation of both antisense dg and dg RNA was reduced in tgs1Δ cells, we concluded that Tgs1 specifically hypermethylates dg and antisense dg RNA in both wild-type and swi6Δ cells. Previously, by analyzing RNAs immunoprecipitated with anti-histone H3 antibody, we showed that hncRNAs were retained on heterochromatin (Kajitani et al, 2017;Nakama et al, 2012). Hence, we examined the contribution of the TMG cap to chromatin binding by hncRNAs.…”
Section: Dg Antisense Transcript Has a Tgs1dependent Tmg Cap Whichmentioning
confidence: 98%